Cross-cultural adaptation and validation of the Spanish version of the Prevent for Work questionnaire - Blasco-Abadía, Julia; Bellosta-López, Pablo; Doménech-García, Víctor; Palsson, Thorvaldur Skuli; Christensen, Steffan Wittrup McPhee; Hoegh, Morten; Berjano, Pedro; Langella, Francesco (Frontiers in Public Health, 2025)
BackgroundMusculoskeletal pain represents an increase in medical expenses due to disability and decreased quality of life among workers. Various biopsychosocial factors contribute to the development of persistent and disabling musculoskeletal pain. The Prevent for Work questionnaire (P4Wq) intended to analyze these factors. In this study, the original Italian version of the P4Wq was translated and culturally adapted to Spanish. Moreover, the psychometric properties were evaluated among Spanish workers with and without recent history of disabling spinal pain.MethodsThe first phase consisted of a forward-and-backward translation process and evaluating the face-validity of the questionnaire among 30 Spanish workers. The second phase involved 153 Spanish workers who completed the P4Wq, Oswestry Disability Index (ODI), and EQ-5D-5L questionnaires. Finally, 50 Spanish workers completed the P4Wq 2 weeks later to evaluate test–retest reliability and measurement error.ResultsMinor changes were made after the forward-and-backward translation process, which ensured that the Spanish versions was face-valid. The P4Wq demonstrated acceptable internal consistency for Spanish version (Cronbach’s alpha: 0.91), a moderate negative association with the indicator of quality of life (ρ < −0.39; p = 0.001) and moderate positive association with the disability index (ρ > 0.46; p = 0.001). Furthermore, the P4Wq showed good to excellent item response stability (weighted kappa = 0.75–0.96) and good for the total score (ICC = 0.98).ConclusionThe Spanish version of the P4Wq was face-valid and exhibited a similar structure as the original version. Additionally, good internal consistency and construct validity were found. This translated version of the questionnaire can therefore be considered acceptable for use by workers with and without history of disabling musculoskeletal pain.